A descriptive study of the attitudes of doctors, working at clinics and day hospitals in the Cape Metropole to patients with HIV/AIDS - Fransman, Desireé Christine (Department of Paediatrics and Child Health, 2017)
HIV/AIDS is a fairly new condition. Despite a large amount of published literature regarding its clinical aspects, there is a paucity of South African research and information relating to the attitudes and feelings of the physicians who diagnose, care for and make decisions with regard to these patients, especially children. Several studies suggest that health care workers who provide clinical care for Persons with HIV/AIDS (PWA's) may have an intolerant attitude towards them. As the number of children with HIV/AIDS increases, the burden of care will shift to health care workers at primary level care. It was therefore decided to assess the attitudes of doctors at primary level care facilities in Cape Town, towards paediatric patients with HIV/AIDS. The results of this study are crucial given the increasing exposure of doctors at this level to HIV/AIDS patients and understanding their response to its management. The objectives of the study were to: assess whether doctors' knowledge of the patient's HIV positive status affects their attitudes and management of the patient; assess doctors' perceived competency with regard to the management of paediatric AIDS; determine doctors' opinions with regard to HIV testing, the utilisation of diagnostic investigations and treatment; determine doctors' main concerns with regard to the management of paediatric patients with HIV/AIDS. A descriptive, cross-sectional survey was conducted amongst all doctors working at the clinics and day hospitals in Cape Town during the period February to April 1997. Seventy-eight doctors (51 % response rate) working in the clinics and day hospitals in Cape Town each completed an anonymous self-administered questionnaire. Doctors in this survey generally displayed a positive, humanistic attitude towards children with HIV/AIDS. In the majority of cases the knowledge of the child 's HIV positive status did not impact negatively on their management of the child. Interestingly, 86% of respondents felt that they would always/mostly take extra care in applying universal precautions when they know that the child is HIV positive. There is a lack of confidence in their counselling and clinical competency in the management of children with HIV/AIDS. The main source of information with regard to paediatric HIV/AIDS is journals (69%), followed by in-service training (53%) and colleagues (49%). In contrast, the preferred sources of information were in-service training (68%) and organised discussion groups/workshops (65%). Most were in favour of routine HIV testing of pregnant women and informed consent for HIV testing. However, not everyone agreed that pre-HIV test counselling was necessary in the case of children. Confidentiality of positive test results was not favoured in the majority of cases (65%) and disclosure even without the consent of the patient/carer was supported. Priority concerns relating to the management of paediatric HIV/AIDS, were lack of support in the community for parents and children, lack of policy and management guidelines and the lack of resources in the health services to cope with the burden of care. This study identifies the need for specific training in HIV/AIDS for medical doctors at primary level care facilities. The foundation of this training must begin with medical students during their clinical years but training and support should continue through in-service training. Training strategies, which address the clinical and psychological challenges presented by this disease, should be employed. In addition, clinical guidelines, which are relevant to South Africa and evidence-based, should be adopted nationally. Resources should be available to support these guidelines. It is further recommended that policies be underpinned by appropriate legislation which protects the rights of patients and health care workers in order to minimise the effects of individual attitudes and biases with regard to the treatment of PWAs.